North Carolina State Agencies Working to Prevent Agricultural Injuries and Illnesses. Issue 4 (2nd October 2017) - Langley, Ricky; Hirsch, Anne; Cullen, Regina; Allran, John; Woody, Renee; Bell, Derrick
ABSTRACT: Over the past 25 years, the North Carolina Departments of Labor, Agriculture and Consumer Services, and Health and Human Services have worked with farmers, farmworkers, commodity and trade associations, universities, and cooperative extension agents to develop programs to decrease the occurrence of injuries and illnesses among agricultural workers and their families. The Bureau of Agricultural Safety and Health in the North Carolina Department of Labor helped craft the Migrant Housing Act, created the Gold Star program, and developed numerous projects promoting rural highway safety and farm safety. The Structural Pest Control & Pesticides Division in the North Carolina Department of Agriculture & Consumer Services administers programs funded by the Pesticide Environmental Trust Fund (PETF), including the Pesticide Container Recycling Program, Pesticide Disposal Assistance Program (PDAP), and Soil Fumigation Training. The Occupational and Environmental Epidemiology Branch (OEEB) in the North Carolina Department of Health and Human Services developed public health surveillance programs for pesticide incidents and carbon monoxide poisoning. These projects, programs, and policies demonstrate the work that North Carolina state agencies are doing to improve the health of agricultural workers and their families.